Analisis Framing Pemberitaan Afif Maulana di Instagram Narasinewsroom - Puspa Izzati Annisa (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study examines the framing strategies employed by the Instagram account @Narasinewsroom in reporting the case of Afif Maulana, a 13 year old boy who allegedly died due to police violence in Padang, Indonesia. Using Robert N. Entman’s framing theory, the research investigates how visual and textual elements on social media define problems, diagnose causes, construct moral judgments, and propose solutions. Adopting a qualitative descriptive approach, the study analyzes five Instagram posts published between July and December 2024 using content analysis methods. The findings indicate that @Narasinewsroom consistently adopts an empathetic tone towards the victim, challenges the credibility of official police narratives, and fosters public solidarity through affective visuals and symbolic rhetoric. These framing practices reflect a deliberate effort to shape public perception, amplify counter narratives, and advocate for justice. Rather than maintaining neutrality, the account positions itself as a critical actor within the digital media landscape, highlighting state violence and systemic injustice. The study concludes that Instagram, as a visually driven platform, serves not only as a space for news dissemination but also as a site of discursive resistance, enabling alternative journalism to thrive in the digital era. This research contributes to the broader understanding of digital activism, framing, and the democratization of public discourse in Southeast Asia.